Tingkat Kepuasan Pasien Rawat Jalan Terhadap Mutu Pelayanan Obat Pada Apotek Pelengkap Kimia Farma Kupang - Muntasir (Jurnal Pangan Gizi dan Kesehatan, 2009)
This research aim to know the level of satisfaction of patient toward the quality of drug services at Apotek Kimia Farma Pelengkap based on its Realibility; Responsiveness; Accuracy; Empathy and Tangible. This is a descriptive research using survey and observational approach. The total number of sample was 100 respondents. Data was analyzed descriptively in the form of frequency distribution tables. The result of the research indicates that the level of Satisfaction to Reliability areequal to 28,33% high gratified, 53,67% gratified, 14,67% low gratified, 3,33 dissatisfactory %; Responsiveness are equal to 45,00% hardly gratified, 37,33% gratified, 13,67% unable to gratify, 4,00 dissatisfactory %; Accuracy are equal to 50,67% hardly gratified, 43,33% gratified, 6,00% unable to gratified, 3,33 dissatisfactory %; Empathy are equal to 53,67% hardly gratified, 45,00% gratified, 1,00% low gratified, 0,33 dissatisfactory %; and Tangible are equal to 43,67% hardly gratified, 56,33% gratified, 0 % unable to gratified, dissatisfactory 0%; Totally the level of satisfaction of patient toward quality of drug service stays at the level high gratified 44,27% and gratified at 47,13%. These results indicates that the level of satisfaction of patient toward quality of drug service at Apotek Kmia Farma Complement has fulfilled drug service impatient hope.